Prevalence and determinants of diarrhea among under-five children in Ethiopia: A systematic review and meta-analysis. - Animut Alebel; Cheru Tesema; Belisty Temesgen; Alemu Gebrie; Pammla Petrucka; Getiye Dejenu Kibret (PLoS ONE)
Background Despite remarkable progress in the reduction of under-five mortality, childhood diarrhea is still the leading cause of mortality and morbidity in this highly susceptible and vulnerable population. In Ethiopia, study findings regarding prevalence and determinants of diarrhea amongst under-five children have been inconsistent. Therefore, this systematic review and meta-analysis estimates the pooled prevalence of diarrhea and its determinants among under-five children in Ethiopia. Methods International databases, including PubMed, Web of Science, EMBASE, CINAHL, Google Scholar, Science Direct, and the Cochrane Library, were systematically searched. All identified observational studies reporting the prevalence and determinants of diarrhea among under-five children in Ethiopia were included. Two authors independently extracted all necessary data using a standardized data extraction format. STATA Version 13 statistical software was used. The Cochrane Q test statistics and I2 test were used to assess the heterogeneity of the studies. A random effects model was computed to estimate the pooled prevalence of diarrhea. Moreover, the associations between determinant factors and childhood diarrhea were examined using the random effect model. Results After reviewing of 535 studies, 31studies fulfilled the inclusion criteria and were included in the meta-analysis. The findings from the 31 studies revealed that the pooled prevalence of diarrhea among under-five children in Ethiopia was 22% (95%CI: 19, 25%). Subgroup analysis of this study revealed that the highest prevalence was observed in Afar region (27%), followed by Somali and Dire Dawa regions (26%), then Addis Abeba (24%). Lack of maternal education (OR: 2.5, 95% CI: 1.3, 2.1), lack of availability of latrine (OR: 2.0, 95%CI: 1.3, 3.2), urban residence (OR: 1.9, 95%CI: 1.2, 3.0), and maternal hand washing (OR: 2.2, 95%CI: 2.0, 2.6) were significantly associated with childhood diarrhea. Conclusion In this study, diarrhea among under-five children in Ethiopia was significantly high. Lack of maternal education, lack of availability of latrine, urban residence, and lack of maternal hand washing were significantly associated with childhood diarrhea.